Impact of Photobiomodulation Therapy Dosing Strategies on Strength, Clinical Outcomes, and Metabolic Responses: A Blinded Randomized Clinical Trial: Incremental dose in PBMT for muscle performance - Girasol, Carlos Eduardo; Caseiro Filho, Luis Carlos; Moraes, José Miguel Andrade Ferraz; inaldi, Mateus Lelé R; Papoti, Marcelo; Guirro, Rinaldo Roberto de Jesus Guirro (Journal of Lasers in Medical Sciences, 2024)
Introduction: Recent evidence suggests that the combination of exercise and photobiomodulation therapy (PBMT) enhances muscle performance, including improvements in strength, hypertrophy, and fatigue resistance. As muscle tissue changes after training, a dose progression over time may show additional effects. However, there needs to be more clarity regarding the optimal physical parameters for enhancing muscle performance. Thus, the aim was to evaluate the impact of strength training combined with PBMT at fixed or progressive doses on strength performance, metabolic activity, and clinical outcomes in healthy individuals. Methods: This was a double-blind, randomized clinical trial. Fifty-six male participants were randomly allocated into four groups: Sham, minimal dose (60 J), maximal dose (300 J), and incremental dose (60–300 J). Baseline assessments included body composition analysis and isokinetic dynamometry (peak torque and total work of the quadriceps femoris and hamstring muscles), followed by ten sessions of strength training combined with PBMT applied before each exercise session, which consisted of three sets of stiff and squats. PBMT irradiation was applied to the quadriceps and hamstrings. Training loads and psychophysiological responses were monitored throughout the intervention. Participants were reassessed at the end of the training period and followed up for a total duration of seven days. Results: No significant differences were observed between the groups in isokinetic strength parameters (P>0.05), although small to moderate effect sizes favored the Incremental and Maximal Dose groups. Similar patterns were found for psychophysiological responses and training loads across the groups. Conclusion: In the context of this research model, PBMT combined with strength training did not yield superior outcomes in muscle strength, psychophysiological, or metabolic parameters compared to the different dosing strategies evaluated.